Pengaruh Board Financial Expertise Terhadap Kualitas Pelaporan Keuangan Pada Perusahaan Manufaktur Subsektor Food and Beverage Yang Terdaftar di Bursa Efek Indonesia - Agnes Julia Kosim; Mutiara Maimunah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study examines the effect of board financial expertise on financial reporting quality in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2022 period. Drawing on agency theory, commissioners with financial backgrounds are expected to strengthen oversight functions, reduce information asymmetry, and improve the overall quality of financial reporting. A quantitative approach was employed using secondary data obtained from companies' annual reports. Sample selection was conducted through purposive sampling, yielding 168 observations following outlier detection. Board financial expertise was operationalized as the proportion of board of commissioners members with an accounting or finance background, while financial reporting quality was proxied by earnings quality measured through total accruals. Data were analyzed using simple linear regression after all classical assumption tests were satisfied. The findings reveal that board financial expertise does not exert a significant influence on financial reporting quality. This suggests that financial competence within the board of commissioners alone is insufficient to meaningfully improve reporting quality, particularly under the pressures of the COVID-19 pandemic. The study underscores the necessity of strengthening broader corporate governance mechanisms to support higher standards of financial reporting